Network Pharmacology with Metabolomics Study to Reveal the Mechanisms of Bushen Huoxue Formula in Intervertebral Disc Degeneration Treatment - Guo J; Yang S; Zhai W; Xie Y; Shen Z; Zhang J; Jia Y (Dove Medical Press, 2024)
Ji Guo,1- 3 Shengqi Yang,1- 4 Weifeng Zhai,1- 3,5 Yue Xie,1- 4 Zhan Shen,1- 4 Jianpo Zhang,1- 3 Yongwei Jia1- 3,5 1Guanghua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 200052, People's Republic of China; 2Shanghai Guanghua Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai, 200052, People's Republic of China; 3Institute of Arthritis Research in Integrative Medicine, Shanghai Academy of Traditional Chinese Medicine, Shanghai, 200052, People's Republic of China; 4Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People's Republic of China; 5Department of Orthopedics, Shanghai University of Medicine & Health Sciences Affiliated Zhoupu Hospital, Shanghai, 201318, People's Republic of ChinaCorrespondence: Ji Guo; Yongwei Jia, Email 153498661@qq.com; spinejia@163.comBackground: Intervertebral disc degeneration (IVDD) is a pathophysiological process that leads to severe back pain or neurological deficits. The Bushen Huoxue Formula (BSHXF) is a traditional herbal remedy widely used to treat diseases related to IVDD. However, its pharmacological mechanism needs further exploration.Objective: This study aimed to elucidate the mechanisms through which BSHXF treats IVDD-related diseases by integrating metabolomics with network pharmacology.Methods: Network pharmacology was utilized to identify potential targets of BSHXF against IVDD. Additionally, an animal model of needle puncture-induced disc degeneration was established to assess the effect of BSHXF. Mice were randomly assigned to the sham group, model group, and BSHXF group. Various techniques, including PCR, CCK-8 assay, MRI, histological examinations, and immunohistochemical analyses, were employed to evaluate degenerative and oxidative stress conditions in mouse disc tissue and cultured nucleus pulposus (NP) cells. UHPLC-HRMS/MS was used to differential distinct metabolites in the disc tissue from different groups, and MetaboAnalyst 5.0 was employed to enrich the metabolic pathways.Results: Through network pharmacology, 15 core proteins were identified through protein-protein interaction (PPI) network construction. Functional enrichment analysis highlighted the critical role of BSHXF in addressing IVDD by influencing the response to oxidative stress. Furthermore, experimental evidence demonstrated that BSHXF significantly improved the pathological progression of IVDD and increased oxidative stress markers SOD-1 and GPX1, both in the disc degeneration model and cultured NP cells. Metabolomics identified differential metabolites among the three groups, revealing 15 metabolic pathways between the sham and model groups, and 13 metabolic pathways enriched between the model and BSHXF groups.Conclusion: This study, integrating network pharmacology and metabolomics, suggests that BSHXF can alleviate IVDD progression by modulating oxidative stress. Key metabolic pathways associated with BSHXF-mediated reduction of oxidative stress include the citrate cycle, cysteine and methionine metabolism, alanine, aspartate and glutamate metabolism, glycine, serine and threonine metabolism, D-glutamine and D-glutamate metabolism, glutathione metabolism, and tryptophan metabolism. While this research demonstrates the therapeutic potential of BSHXF in reducing oxidative stress levels in IVDD, further research is needed to thoroughly understand its underlying mechanisms.Keywords: metabolomics, network pharmacology, intervertebral disc degeneration, oxidative stress, Bushen Huoxue formula